2019
DOI: 10.17712/nsj.2019.1.20180303
|View full text |Cite
|
Sign up to set email alerts
|

Is cesarean section delivery associated with autism spectrum disorder?

Abstract: Objectives: To investigate a correlation between birth by caesarean section and autism spectrum disorder (ASD). Methods: A case-control study with a case to control ratio of 1:2 was performed in Al-Madina Al-Munawarah city, Kingdom of Saudi Arabia during the year 2016. The cases were selected according to the eligibility criteria and children attending a wellbaby clinic in the same hospital, were chosen as the control group subjects. Data was collected from the medical records and an interview-based questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…Findings in our study showed an association between autism and mode of delivery, the odds of autism is higher among those born via Csection compared to those born via normal deliveries. Our results concur with the findings from the study conducted by Al-Zalabani et al (2019), in which the OR value was reported to be 2.9, after adjusting for potential confounders. This finding is similar to the results reported in the systematic review by Curran et al (2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Findings in our study showed an association between autism and mode of delivery, the odds of autism is higher among those born via Csection compared to those born via normal deliveries. Our results concur with the findings from the study conducted by Al-Zalabani et al (2019), in which the OR value was reported to be 2.9, after adjusting for potential confounders. This finding is similar to the results reported in the systematic review by Curran et al (2015).…”
Section: Discussionsupporting
confidence: 92%
“…Although the causal relationship between the type of obstetric delivery and ASD is not established, there is some evidence of association between the two. It has been observed that Caesarean section tend to increase the risk of ASD ( Al-Zalabani et al., 2019 ; Curran et al., 2015 , 2016 ; Gregory et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to this study, delivery by CS was associated with a higher risk of ASD in children, even after adjusting the potential confounding factors. The result was supported by previous well-established observations that increased risk of ASD was associated with delivery by CS [13,27,29]. Further sex stratification analysis revealed a sex-biased ratio in the risk of developing ASD among births by CS, irrespective of the different surgical indications and method of anesthesia.…”
Section: Discussionsupporting
confidence: 85%
“…A recent metaanalysis demonstrated that a 23% increase in the risk of ASD was associated with CS compared to vaginal delivery [10]. Even though previous studies have reported that CS is not a risk factor for ASD [11,12], most studies have reached a consistent conclusion [13,14]. The incidence of CS is increasing globally, with an evaluated annual increase of 4% [15].…”
Section: Introductionmentioning
confidence: 99%
“…A large percentage of cases were delivered via Caesarean section. This may skew results as this mode of delivery has previously been associated with increased ASD incidence (Al-Zalabani et al, 2019 ; Curran et al, 2015a , 2015b ; Morais et al, 2020 ). Larger, longer-term studies, which take long-term outcomes into account will be required with repeated maternal cytokine profiling to attempt to replicate and expand our findings.…”
Section: Discussionmentioning
confidence: 99%